Prevalence and severity of laryngeal collapse in dogs undergoing surgery for brachycephalic obstructive airway syndrome: 80 dogs (2018–2022) - Gallant, Courtney; Phipps, Whitney (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to determine the incidence and severity of laryngeal collapse in brachycephalic breeds presented for surgical management of brachycephalic obstructive airway syndrome (BOAS). The primary hypothesis was that French Bulldogs would have a higher incidence of laryngeal collapse than the other breeds and a higher stage of laryngeal collapse at presentation. The second hypothesis was that higher stages of laryngeal collapse would be associated with increased perioperative complications.MethodsClinical records of dogs referred for surgical intervention of BOAS from a single institution were retrospectively reviewed from January 2018 to December 2022. Signalment, physical examination, stage of laryngeal collapse, surgical procedures, the occurrence of postoperative complications, and short-term outcomes were recorded.ResultsFrench bulldogs were the most common breed presented (53.75%). Fifteen dogs (18.75%) had no evidence of laryngeal collapse, 46 dogs (57.50%) had stage I laryngeal collapse, 13 dogs (16.25%) had stage II laryngeal collapse, and six dogs (7.50%) had stage III laryngeal collapse. There was no association between breed and stage of laryngeal collapse (p = 0.68). Postoperative complications were seen in 25/80 (31.25%) dogs. A higher stage of laryngeal collapse was associated with an increased risk of postoperative complications (p < 0.0001), including regurgitation, temporary tracheostomy, oxygen supplementation, and aspiration pneumonia. No association was found between additional procedures performed and the incidence of postoperative complications (p = 0.31).DiscussionFrench bulldogs were the most common breed seen for BOAS surgery during this period. Dogs with a higher stage of laryngeal collapse were at an increased risk of developing postoperative complications. Owners should be counseled that the risks of surgery may be higher with higher stages of laryngeal collapse. Further studies are indicated to evaluate the long-term prognosis.